PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL: TINJAUAN HUKUM TIKTOK SHOP - Sukoco, Gilang Panji (Cahaya Ilmu Bangsa, 2024)
Examining the current state of intellectual property protection laws in Indonesia as they pertain to Tiktok Shop accounts is the primary objective of this study. This study employs a descriptive qualitative methodology. According to the data, Tiktok is now the most popular social networking platform. Owner of the capital uses it to operate his web company. Tiktok Shop and the Preservation of Intellectual Property Are Both Overseen by Law Intellectual property rights (IPR) and intangible items go hand in hand because of the content and the need to safeguard creations that are the result of human imagination. Creative businesses may benefit from intellectual property rights in the long run from financial investments. Regarding intellectual property rights that stem from rational thought. In intellectual property rights (IPR), the four main pillars are literature, art, science, and technology. No. 28/2014, Patent Law no. 13/2016, No. 20/2016, Plant Variety Protection Law/2000, No. 30/2000, Industrial Design Law 31/2000, and No. 28/2014 are some of the laws and regulations that govern intellectual property rights.